2016
DOI: 10.3389/fvets.2016.00063
|View full text |Cite
|
Sign up to set email alerts
|

Applications of In Ovo Technique for the Optimal Development of the Gastrointestinal Tract and the Potential Influence on the Establishment of Its Microbiome in Poultry

Abstract: As the current poultry production system stands, there is a period of time when newly hatched chicks are prevented from access to feed for approximately 48–72 h. Research has indicated that this delay in feeding may result in decreased growth performance when compared to chicks that are fed immediately post-hatch. To remedy this issue, in ovo methodology may be applied in order to supply the embryo with additional nutrients prior to hatching and those nutrients will continue to be utilized by the chick post-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 145 publications
(174 reference statements)
3
106
0
3
Order By: Relevance
“…Dietary pre biotics, including inulin, yeast cell wall extracts, lactulose and GOS are usually fed at concentrations up to 0.2% (weight/volume) of diet [140][141][142][143][144][145][146] .…”
Section: Conferring a Health Benefitmentioning
confidence: 99%
“…Dietary pre biotics, including inulin, yeast cell wall extracts, lactulose and GOS are usually fed at concentrations up to 0.2% (weight/volume) of diet [140][141][142][143][144][145][146] .…”
Section: Conferring a Health Benefitmentioning
confidence: 99%
“…Early chick feeding is essential, and research reports reveal that delayed feeding access led to decreased growth rate, reduced feed conversion efficiency, extended the time of marketing body weight (BW), and increased the mortality . On the other hand, early intake of external feed after hatching is associated with rapid development of organs and GI tract . The GI tract is the most rapidly developing organ in the later stage of incubation, making up to 1% of the weight of the 18‐day‐old embryo and reaching 3.5% at hatch …”
Section: Introductionmentioning
confidence: 99%
“…Controversially, Roto et al (2016) emphasize that in situations of high temperatures, the opposite is observed, that is, there is a reduction in the weight of the intestine, as a consequence of a physiological adjustment in an attempt to reduce the production of corporal heat.…”
Section: Resultsmentioning
confidence: 99%
“…The period immediately after hatching is crucial for the development of chicks due mainly to the morphophysiological events of the gastrointestinal tract (Boleli, Maiorka, & Macari, 2008;Roto, Kwon, & Ricke, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation